Kontribusi Retribusi Tempat Rekreasi Dan Olahraga Dalam Meningkatkan Pendapatan Asli Daerah Di Kabupaten Ngawi - Sarjiyati, Sarjiyati; Haryani, Anik Tri; Dyah A, Enda Warna (Universitas Merdeka Madiun, 2020)
The purpose of this study was to determine the regulation of levies for recreational and sporting places in Ngawi Regency and the contribution levy of recreational and sporting place fees in increasing local revenue in Ngawi Regency in 2014-2018. The type of method used in this research is normative research, with the method of statute approach, the legal materials in this study are primary, secondary and tertiary legal materials, through interview and documentation data collection techniques, with qualitative analysis. The regulation of recreational and sporting levies in Ngawi Regency has changed in structure and the amount of the retribution tariff is due to the addition of two recreational and sporting objects so that there are five recreational and sporting object levies owned by the Regional Government of Ngawi Regency. The contribution of recreational and sporting place fees in increasing local revenue in Ngawi Regency in 2014 was 0.58%, in 2015 amounted to 0.57%, in 2016 amounted to 0.64%, in 2017 amounted to 0.28% and in 2018 amounted to 0.96%. Recreation and sports places that contribute the highest retribution are Tawun, Alun - alun, Trinil Museum, Ketonggo Stadium and GOR Bung Hatta.